N-Oxy lipid-based click chemistry for orthogonal coupling of mannan onto nanoliposomes prepared by microfluidic mixing: Synthesis of lipids, characterisation of mannan-coated nanoliposomes and in vitro stimulation of dendritic cells - Bartheldyová, Eliška; Turánek Knotigová, Pavlína; Zachová, Kateřina; Mašek, Josef; Kulich, Pavel; Effenberg, Roman; Zyka, Daniel; Hubatka, František; Kotouček, Jan; Čelechovská, Hana; Héžová, Renata; Tomečková, Andrea; et al. (Carbohydrate polymers, 2019)
New synthetic aminooxy lipid was designed and synthesized as a building block for the formulation of functionalised nanoliposomes (presenting onto the outer surface of aminooxy groups) by microfluidic mixing. Orthogonal binding of cellular mannan (Candida glabrata (CCY 26-20-1) onto the outer surface of functionalised nanoliposomes was modified by orthogonal binding of reducing termini of mannans to oxime lipids via a click chemistry reaction based on aminooxy coupling (oxime ligation). The aminooxy lipid was proved as a suitable active component for preparation of functionalised nanoliposomes by the microfluidic mixing method performed with the instrument NanoAssemblrTM. This "on-chip technology" can be easily scaled-up. The structure of mannan-liposomes was visualized by transmission and scanning electron microscopy, including immunogold staining of recombinant mannan receptor bound onto mannosylated-liposomes. The observed structures are in a good correlation with data obtained by DLS, NTA, and TPRS methods. In vitro experiments on human and mouse dendritic cells demonstrate selective internalisation of fluorochrome-labelled mannan-liposomes and their ability to stimulate DC comparable to lipopolysaccharide. We describe a potentially new drug delivery platform for mannan receptor-targeted antimicrobial drugs as well as for immunotherapeutics. Furthermore, the platform based on mannans bound orthogonally onto the surface of nanoliposomes represents a self-adjuvanted carrier for construction of liposome-based recombinant vaccines for both systemic and mucosal routes of administration.
Keywords: antigeny povrchové; Animals; velikost částic; Mannose-Binding Lectins; Candida glabrata; Lectins, C-Type; mannany; mikrofluidika; Adjuvants, Immunologic; Dendritic Cells; dendritické buňky; Liposomes; lipidy; Nanoparticles; Particle Size; lidé; lektiny typu C; Lipids; Mice, Inbred BALB C; nanočástice; hydroxylaminy; liposomy; myši inbrední BALB C; receptory buněčného povrchu; Click Chemistry; Microfluidics; Receptors, Cell Surface; lektiny vázající mannosu; zvířata; Antigens, Surface; Mannans; adjuvancia imunologická; Hydroxylamines; click chemie; Humans